"I'll Try My Best to be a Dad": The Experiences of Japanese Fathers with Cancer. (January 2021) - Tamura, Rika; Yamazaki, Tomoko; Uchibori, Mayumi
This study explored the experiences of Japanese fathers with cancer. Twenty-four adult men undergoing cancer treatment and raising minor children (aged ≤ 19 years) participated. Data gathered using semi-structured interviews were analyzed using the grounded theory approach. One main theme— "transformed identity: cancer made me into a father"—and eight additional sub-themes were identified from the analysis. Fathers with cancer experienced changes in work and income; weakening of their bodies and minds; and a transformation from the protector of their children to the protected, which severely challenging their identities. Through interaction with their children and self-reflection, fathers started to examine fatherhood for the first time, heightening their self-awareness as fathers. Nurses can support fathers by facilitating interactions with their children while receiving treatment and by understanding and respecting the range of emotions identified in this study.